Profile of Exosomal and Intracellular microRNA in Gamma-Herpesvirus-Infected Lymphoma Cell Lines - Hoshina, Shiho; Sekizuka, Tsuyoshi; Kataoka, Michiyo; Hasegawa, Hideki; Hamada, Hiromichi; Kuroda, Makoto; Katano, Harutaka (PloS one, 2016)
Exosomes are small vesicles released from cells, into which microRNAs (miRNA) are specifically sorted and accumulated. Two gamma-herpesviruses, Kaposi sarcoma-associated herpesvirus (KSHV) and Epstein-Barr virus (EBV), encode miRNAs in their genomes and express virus-encoded miRNAs in cells and exosomes. However, there is little information about the detailed distribution of virus-encoded miRNAs in cells and exosomes. In this study, we thus identified virus- and host-encoded miRNAs in exosomes released from KSHV- or EBV-infected lymphoma cell lines and compared them with intracellular miRNAs using a next-generation sequencer. Sequencing analysis demonstrated that 48% of the annotated miRNAs in the exosomes from KSHV-infected cells originated from KSHV. Human mir-10b-5p and mir-143-3p were much more highly concentrated in exosomes than in cells. Exosomes contained more nonexact mature miRNAs that did not exactly match those in miRBase than cells. Among the KSHV-encoded miRNAs, miRK12-3-5p was the most abundant exact mature miRNA in both cells and exosomes that exactly matched those in miRBase. Recently identified EXOmotifs, nucleotide motifs that control the loading of miRNAs into exosomes were frequently found within the sequences of KSHV-encoded miRNAs, and the presence of the EXOmotif CCCT or CCCG was associated with the localization of miRNA in exosomes in KSHV-infected cells. These observations suggest that specific virus-encoded miRNAs are sorted by EXOmotifs and accumulate in exosomes in virus-infected cells.